Single-Cell Transcriptomics Identifies Brain Endothelium Inflammatory Networks in Experimental Autoimmune Encephalomyelitis. Issue 1 (29th January 2023) - Fournier, Antoine Philippe; Tastet, Olivier; Charabati, Marc; Hoornaert, Chloé; Bourbonnière, Lyne; Klement, Wendy; Larouche, Sandra; Tea, Fiona; Wang, Yu Chang; Larochelle, Catherine; Arbour, Nathalie; Ragoussis, Jiannis; et al.
Abstract : Background and Objectives: Multiple sclerosis (MS) is a neuroinflammatory and neurodegenerative disease characterized by infiltration of immune cells in multifocal areas of the CNS. The specific molecular processes allowing autoreactive immune cells to enter the CNS compartment through the blood-brain barrier remain elusive. Methods: Using endothelial cell (EC) enrichment and single-cell RNA sequencing, we characterized the cells implicated in the neuroinflammatory processes in experimental autoimmune encephalomyelitis, an animal model of MS. Validations on human MS brain sections of the most differentially expressed genes in venous ECs were performed using immunohistochemistry and confocal microscopy. Results: We found an upregulation of genes associated with antigen presentation and interferon in most populations of CNS-resident cells, including ECs. Interestingly, instead of transcriptionally distinct profiles, a continuous gradient of gene expression separated the arteriovenous zonation of the brain vasculature. However, differential gene expression analysis presented more transcriptomic alterations on the venous side of the axis, suggesting a prominent role of venous ECs in neuroinflammation. Furthermore, analysis of ligand-receptor interactions identified important potential molecular communications between venous ECs and infiltrated immune populations. To confirm the relevance of our observation in the context of human disease, we validated the protein expression of the most upregulated genes ( Ackr1 and Lcn2 ) in MS lesions. Discussion: In this study, we provide a landscape of the cellular heterogeneity associated with neuroinflammation. We also present important molecular insights for further exploration of specific cell processes that promote infiltration of immune cells inside the brain of experimental autoimmune encephalomyelitis mice.